Analysis of Drinking Water Quality among Employees of Sulianti Saroso Infectious Disease Hospital - Nurlaela; Setyawati, Fajar Dwi; Pratiwi, Tiara Zakiyah; Haryadi, Eko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Drinking water is water through or without processing that meets health requirements and can be drunk directly. The aim of the study is to check the quality of drinking water for employees of Sulianti Saroso Infectious Disease Hospital (SSIDH) so that it is suitable or not for consumption in accordance with established quality standards. Drinking water sampling is carried out twice a year with a sampling point of 8 (eight) samples at every 6 (six) months. Based on the results of physical tests, namely smell, turbidity, taste, temperature, total dissolved solids, and color, it shows that the employee's drinking water has met the quality standards according to applicable regulations. Chemical drinking water quality requirements show pH concentrations ranging from 7.22 – 8 and other parameters including organic substances have met the quality standard requirements. Biological test results show the bacteriological quality of drinking water Total Coliform and Escherichia Coli is 0 according the required quality standard of 0 per 100 ml. The quality of drinking water for employees of RSPI Prof. Dr. Sulianti Saroso based on the results of laboratory examinations shows 100% of samples meet the requirements in accordance with the drinking water quality standard.